Fuzzy ABC: modeling the uncertainty in environmental cost allocation - Borba, José Alonso (2007)
In many cases, preventing pollution and environmental destruction is cheaper than remedying these damages. In this sense, environmental cost allocation enables a better visualization and analysis of a product's profitability. However, the environmental allocation process involves estimated information and assumes linearity between activity consumption and product that is not real in many cases. In order to handle this not-linearity, this research presents a methodology based on fuzzy logic concepts in order to model both the subjectivity and uncertainty inherent in the environmental allocation process. A case from Hansen and Mowen (2001, p. 584) has been used as a reference for the construction of the fuzzy model. Following, new variables were incorporated, and a proposed solution was developed utilizing fuzzy logic concepts. A total of 126 inference rules were created with the help of the specific software FuzzyTECH®, which resulted in the new cost drivers that were used to allocate the environmental costs to the products. The results founded in the proposed model FuzzyABC (Fuzzy Activity Based Costing) show that fuzzy logic can be used as a helpful tool in environmental cost allocation due to the ambiguity and subjectivity inherent in these process. Key-words: Environmental Costs. Fuzzy Logic. Activity based Costing. Cost Allocation. Environmental Accounting.